Model Implementasi Kebijakan Recognisi Pembelajaran Lampau: Studi Kasus di Universitas Terbuka - Milwan, Milwan; Andini, Laras Ayu; Sunarya, Amud; Awinda, Syafila Nur; Prasetyo, Eric Adam (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The study examines the implementation of the Recognition of Prior Learning (RPL) policy at Universitas Terbuka (UT) as an effort to enhance higher education access in Indonesia. The background of this research stems from the necessity to acknowledge formal, non-formal, and informal learning experiences according to existing regulations. Over the past five semesters, there was fluctuation in both RPL application numbers and rejection rates. Notably, although the number of rejected applications totaled 967 cases despite being a small percentage (0.9%), this still negatively impacted UT due to many applicants failing to register courses or canceling their enrollment altogether.The aim of this research is to analyze the implementation models of RPL policies and factors influencing them at UT. Using qualitative methods involving deep interviews and document analysis across three locations: Jakarta, Surabaya, and Palembang. The findings reveal significant challenges in implementing RPL policies at UT including difficulties among students understanding RPL requirements and incomplete administrative documents. Despite fluctuations in application numbers, low rejection rates were observed; however ineffective communication and socialization hindered acknowledgment processes significantly. Conclusions stress improvements needed in informational systems and admission applications facilitating student candidates' progress. Additionally emphasizing increased transparency and accountability throughout evaluation processes ensures educational quality maintenance. Recommendations suggest developing new implementation models responsive towards student needs enhancing efficiency/effectiveness within UT's RPL programs.